Formation of AR-SMRT binding in prostate cancer cells treated with natural histone deacetylase inhibitor - Smešný Trtková, Kateřina; Pašková, Lenka; Matiješčuková, Natálie; Kolář, Zdeněk (Disease markers. Section A, Cancer Biomarkers, 2010)
Signaling through the androgen receptor (AR) plays a critical role in prostate cancer progression. The AR is a classical nuclear receptor (NR) providing a link between signaling molecule and transcription response. Histone deacetylase inhibitors (HDACI) have antiproliferative and proapoptotic effects on prostate cancer cells and their implication in silence AR signaling may have potential therapeutic use. We aimed to study the inhibitory effects of the corepressor SMRT (Silencing Mediator for Retinoid and Thyroid hormone receptors) which forms a complex together with nuclear receptor corepressor (N-CoR) and with histone deacetylase 3 (HDAC3) on AR activity. The androgen-sensitive prostate cancer cell line LNCaP and androgen-insensitive prostate cancer cell line C4-2 both AR-positive, and androgen-insensitive DU145 and PC3 prostate cancer cell lines were treated with two HDACIs, sodium butyrate (NaB) and/or trichostatin A (TSA). We amplified immunoprecipitated DNA by conventional PCR and in the following step we used the chromatin immunoprecipitation (ChIP) analysis coupled with quantitative PCR for monitoring NaB induced formation of AR-SMRT/N-CoR complex binding on the PSA promoter. The co-immunoprecipitation assay revealed increase in AR-SMRT formation in NaB treated cells. Simultaneously, the Western blot analysis showed a significant decrease in AR protein expression. Furthermore, we estimated the reduced presence of HDAC2 and HDAC3 proteins by NaB and TSA treatment in AR-negative DU145 cell line. In conclusion, the inhibitory effect of NaB on AR gene expression seems to be specific and unique for prostate cancer AR-positive cell lines and corresponds with its ability to stimulate AR-SMRT complex formation. We suggest that AR and SMRT/N-CoR corepressors may form a stable complex in vitro and NaB may facilitate the interaction between AR nuclear steroid receptor and SMRT corepressor protein.
Keywords: Prostatic Neoplasms; imunoprecipitace; nádory prostaty; regulace genové exprese u nádorů; Humans; Histone Deacetylase Inhibitors; Histone Deacetylase 2; Nuclear Receptor Co-Repressor 2; histondeacetylasy; korepresor 2 jaderného receptoru; Protein Binding; Dose-Response Relationship, Drug; lidé; Histone Deacetylases; androgenní receptory; časové faktory; kyseliny hydroxamové; Male; Butyrates; inhibitory histondeacetylas; butyráty; vazba proteinů; Receptors, Androgen; nádorové buněčné linie; vztah mezi dávkou a účinkem léčiva; histondeacetylasa 2; Cell Line, Tumor; Hydroxamic Acids; Immunoprecipitation; mužské pohlaví; Gene Expression Regulation, Neoplastic; Time Factors